The Ethical Design of an AIDS Vaccine Trial in Africa - Christakis, Nicholas A. (The Hastings Center report, 1988)
Proper conduct of an AIDS vaccine trial in Africa must be informed not only by the epidemiology and biology of HIV infection in African settings, but also by the ethical norms and cultural constraints prevailing in African settings.